Laboratorium : programmaboek - Obrist, Hans Ulrich; Judong, Anne; De Brandt, Gileen; Cusse, Kaatje; Vanderlinden, Barbara; Provinciaal Museum voor Fotografie, Antwerpen (Antwerpen : Antwerpen open, 1999)
François, Michel ; Baltz, Lewis ; Bamgboyé, Oladélé ; Bayrle, Thomas ; Bijker, Wiebe E. ; Collins, Henry M. ; Cornelis, Jef ; Daems, Anne ; Dean, Tacita ; Despret, Vinciane ; Estève, Lionel ; Fabre, Jan ; Farocki, Harun ; Feldmann, Hans-Peter ; Fischli, Peter ; Weiss, David ; et al.
27/06/1999-03/10/1999, Antwerpen, Provinciaal Museum voor Fotografie
kunstcatalogus